2022
DOI: 10.1038/s41598-022-13971-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal gastrointestinal nematode infection enhances spatial memory of uninfected juvenile mouse pups

Abstract: The developing brain is particularly vulnerable to factors including maternal infection during pregnancy. Establishment of neural networks critical for memory and cognition begins during the perinatal period, when Heligmosomoides bakeri, a gastrointestinal (GI) nematode restricted to the maternal mouse intestine, has been shown to upregulate expression of long-term potentiation genes in the young rodent pup brain. We explored the impact of maternal infection during pregnancy and early lactation on the spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
32
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(48 citation statements)
references
References 93 publications
12
32
2
Order By: Relevance
“…CaMKIIα and β and PKCα have distinct and crucial roles in neuronal plasticity and memory; loss of CaMKIIα, CaMKIIβ [56][57][58][59] or PKCα [55] result in severe LTP and spatial memory impairments. Taken together, higher expression of Gria1 and Grin2a, lower expression of Gria4, with higher expression of Camk2a, Camk2b and Prkca would be expected to promote LTP, as demonstrated here, and facilitate spatial memory in response to maternal infection, as we previously reported [10] .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…CaMKIIα and β and PKCα have distinct and crucial roles in neuronal plasticity and memory; loss of CaMKIIα, CaMKIIβ [56][57][58][59] or PKCα [55] result in severe LTP and spatial memory impairments. Taken together, higher expression of Gria1 and Grin2a, lower expression of Gria4, with higher expression of Camk2a, Camk2b and Prkca would be expected to promote LTP, as demonstrated here, and facilitate spatial memory in response to maternal infection, as we previously reported [10] .…”
Section: Discussionsupporting
confidence: 81%
“…Our lab has focused on the in uence of maternal GI nematode infection upon neurodevelopment and cognitive function in offspring, using the murine laboratory model Heligmosomoides bakeri (also known as Heligmosomoides polygyrus), a strictly intestinal nematode with a direct lifecycle [9] . Maternal H. bakeri infection allowed 17 day-old offspring to retain object location memories for 3 hours and three week-old offspring to retain long-term spatial reference memories for 7 days, in contrast to offspring of uninfected dams who could not retain these memories [10] . As rodents are not capable of retaining object location memories for 2 + hours until postnatal day (PD) 24, nor can they retain long-term spatial reference memories for 7 days until PD 60 [11,12] , these ndings suggested that the maturational processes needed to recall these spatial memories were accelerated in response to maternal H. bakeri infection [10] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As early as the 1990s, there was interest in whether helminths influenced host cognition (Townsend et al 2022). Recently, maternal infection with H. bakeri was shown to improve spatial memory of uninfected mouse offspring (Noël et al 2022). After a repeated trickle infection during pregnancy and lactation, spatial learning and memory of the uninfected pups were tested beginning at 23 days of age using a Barnes Maze.…”
Section: Helminths Affect Host Behaviourmentioning
confidence: 99%